Outcome analysis of cross-pinning versus lateral pinning and various lateral pinning configuration in the treatment of displaced paediatric supracondylar humerus fracture - Paramasivam, Deva; Ramachandran, Thirunthaiyan; Ravindranath, Tarun Prashanth; Raja, Doraikumar; Sellakrishnan, Aravindh (International Journal of Research in Orthopaedics, 2022)
Background: Supracondylar humerus fracture accounts for 3% of all the paediatric fractures. Displaced fractures need usually closed but rarely open reduction and stabilization with k-wires by either cross or lateral pinning technique. Controversies prevail regarding the type of pinning which will reduce complications (such as ulnar nerve palsy and loss of reduction which will lead to cubitus varus deformity) and provides better functional and radiological outcome. The aim of study was to analyse outcomes of various pinning techniques in displaced supracondylar humerus fracture treatment. Methods: This was a prospective study done in SRIHER, Chennai (January 2019 to September 2020) included children with displaced supracondylar humerus fracture (modified Gartland type 2B,3). Preop, postop and intraop assessment were done with respect to incidence of ulnar nerve palsy, Baumann’s angle, Flynn criteria till 14 weeks postop period. The results of cross pinning and lateral pinning group were statistically compared. Results: There were totally 37 (male-25, female-12) patients. Mean age was 5.6. The mean change in Baumann’s angle of cross pin and lateral pin group at 14 weeks postop period comparing immediate postop period were 4.13 and 4.15 degrees, which was statistically insignificant using Mann Whitney test (p>0.05). Flynn criteria at 14 weeks postop period between two groups were also statistically insignificant. Difference in Baumann’s angle at 14 weeks postop period between divergent (2.82) and parallel (5.53) pin group was statistically significant using Mann Whitney test (0.01). There were no cases of ulnar nerve injury in both the groups. Conclusions: Lateral pinning technique with the use of 3 divergent pins for the treatment of displaced supracondylar humerus fracture gives stability as good as cross pin configuration and also avoids the risk of ulnar nerve injury.